How to involve carers in the acute care: An online training for clinicians across four sites in England - E. Petkari; A. Kouroupa; D. Giacco (European Psychiatry, 2022)
Introduction Involving carers in the care of people with severe mental illness is known to bring positive treatment and psychosocial outcomes. However, evidence-based procedures to guide clinicians on how to involve carers in the acute care are lacking.